THE EFFECT OF BODY FAT PERCENTAGE ON VO2MAX IN FACULTY OF MEDICINE STUDENTS AT THE UNIVERSITY OF LAMPUNG - Nur Fiana, Dewi; Sofiana Putri, Muflikha (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Changes in lifestyle and high levels of stress in early semester medical students have the potential to increase the risk of obesity which will have a direct effect on increasing the body fat percentage due to inadequate physical activity. The body fat percentage sufficiently affects maximal oxygen uptake (VO2max) during exercise. This study aims to determine the effect of body fats percentage on VO2max in medical students at the University of Lampung. This research is a correlative analytic research with a cross-sectional approach, using primary data obtained from a simple random sampling technique. A total of 39 male students from the Faculty of Medicine of Lampung University batch 2022 who met the inclusion and exclusion criteria were measured for BMI and the body fat percentage using a stepping scale, followed by the measurement of VO2max using the Balke Test method. The results of this study indicate that there is a significant relationship between the body fat percentage to VO2max with a correlation coefficient (r) -0.800, a significant significance value of p<0.000. The correlation formed is - 0.800 indicating a very strong negative correlation between variables, meaning that the higher the body fat percentage, the lower the VO2max values, and vice versa.